Ceramiche vicinorientali della Collezione Popolani - Anastasio, Stefano (Collezione Orientale del Museu Archaeologico Nazionale di Firenze, 2016)
This volume illustrates the Popolani Collection at the Archaeological Museum of Florence, consisting of ancient pottery vessels, terracotta oil-lamps, glazed Islamic tiles, Romano-Byzantine glassware, as well as various objects from the Damascene antique market.